Aerobic Training Improves Angiogenic Potential Independently of Vascular Endothelial Growth Factor Modifications in Postmenopausal Women - Izzicupo, Pascal; D’Amico, Maria A.; Di Blasio, Andrea; Napolitano, Giorgio; Nakamura, Fabio Y.; Di Baldassarre, Angela; Ghinassi, Barbara (Frontiers in Endocrinology, 2017)
Purpose: To evaluate the effect of walking-training on the balance between pro- and anti-angiogenic signals and on the angiogenic potential in postmenopausal women. Materials and Methods: Thirty-four postmenopausal women (56.18 ± 4.24 yr) participated in a 13 weeks program of walking-training. Anthropometric measures, VEGF, IL-1α, IL-1ß, IL-2, IL-8, IL-10, IL-12p70, TNF-α, C-reactive protein, insulin, IGF-1, cortisol, DHEA-S, leptin, visfatin, resistin and adiponectin were evaluated before and after training. Moreover, serum samples were tested for their ability to chemo – attract endothelial cells and to support the in vitro formation of capillary – like structures. Results: After training, the levels of IL-8, TNF-α, leptin and resistin were significantly lower, levels of DHEA-S and adiponectin increased, serum angiogenic properties improved, whereas no changes in anthropometric parameters or VEGF were detected. Conclusions: Walking training reduces inflammatory status and leads to a significant improvement in serum angiogenic properties in the absence of modifications in body composition and VEGF level.